Visas to Dream: Expectations and Emotions of Adolescents and Young People Migrating Alone - Segú Odriozola, Mabel; Gómez-Quintero, Juan David; Casado Patricio, Elena; Aurrekoetxea-Casaus, Maite (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2023)
Most research on adolescents and young people who migrate alone focuses on the causes and conditions of their migratory journey and their settlement in destination societies. However, there is little work that addresses their expectations for the future and, especially, the emotions aroused by their future projects. The aim of the research is to identify their expectations and analyse the emotions linked to them. The methodology consists of the qualitative analysis of 118 interviews carried out in seven Autonomous Communities in Spain, based on categories of analysis such as expectations of migration, future projects and emotions experienced. The results point to the existence of three sets of expectations: material-functional, symbolic-ideal and affective-territorial. The study also points out that, despite the emergence of a wide range of emotions, the most recurrent are suffering, uncertainty and a sense of pride in what they have been able to do. This study contributes to broadening the view of youth migration from a qualitative perspective that allows us to understand the complex web of dreams, projects, fears and suffering experienced by adolescents and young people who have migrated alone to Spain.
Keywords: youth migration; unaccompanied foreign minors; future expectations; emotions; adolescents and young people